Cardiogenic shock and radial access in patients with an acute ST elevation myocardial infarction. (25th November 2020) - Zahn, R; Hochadel, M; Schumacher, B; Pauschinger, M; Stellbrink, C; Schaechinger, V; Behrens, S; Mudra, H; Elsaesser, A; Zeymer, U
Abstract: Background: Cardiogenic shock (CS) in patients (pts) with acute ST elevation myocardial infarction (STEMI) is the strongest predictor of hospital mortality. Radial in contrast to femoral access in STEMI pts might be associated with a lower mortality. However, little is known on radial access in CS pts. Methods: We retrospectively analysed all STEMI pts between 2009 and 2015 who sufferend from CS and who were included into the ALKK PCI registry. Pts treated via a radial access were compared to those treated via a femoral access. Results: Between 2009 and 2015 23796 STEMI pts were included in the registry. 1763 (7.4%) of pts were in CS. The proportion of radial access was 6.6%: in 2009 4.0% and in 2015 19.6%, p for trend <0.0001 with a strong variation between the participating centres (0% to 37%). Conclusions: Radial access was only used in 6.6% of STEMI pts presenting in CS. However, a significant increase in the use of radial access was observed over time (2009: 4%, 2015 19.6%, p<0.001), with a great variance in its use between the participating hospitals. Despite similar pt characteristics the difference in hospital mortality according to access site has to be interpretated with caution. Funding Acknowledgement: Type of funding source: None